2016
DOI: 10.1017/s0031182016000706
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic effects of forage chicory (Cichorium intybus) against gastrointestinal nematode parasites in experimentally infected cattle

Abstract: Two experiments studied the effects of dietary chicory against gastrointestinal nematodes in cattle. In Experiment (Exp.) 1, stabled calves were fed chicory silage (CHI 1 ; n = 9) or ryegrass/clover hay (CTL 1 ; n = 6) with balanced protein/energy intakes between groups. After 16 days, all calves received 10 000 Ostertagia ostertagi and 66 000 Cooperia oncophora thirdstage larvae (L3) [day (D) 0 post-infection (p.i.)]. In Exp. 2, calves were assigned to pure chicory (CHI 2 ; n=10) or ryegrass/ clover (CTL 2 ; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 59 publications
(94 reference statements)
1
34
0
Order By: Relevance
“…Therefore, and considering the relevance of IVM and other anthelmintics for nematode control in Danish cattle, the true extent of AR in bovine nematodes in Denmark needs to be assessed in larger surveys. Until then, producers and veterinarians should be aware of potentially ineffective treatments against GIN in cattle, while reducing the reliance on anthelmintics by including other parasite control strategies with documented efficacy, such as grazing management and feeding with bioactive forages (Nansen et al., 1987, Peña-Espinoza et al., 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, and considering the relevance of IVM and other anthelmintics for nematode control in Danish cattle, the true extent of AR in bovine nematodes in Denmark needs to be assessed in larger surveys. Until then, producers and veterinarians should be aware of potentially ineffective treatments against GIN in cattle, while reducing the reliance on anthelmintics by including other parasite control strategies with documented efficacy, such as grazing management and feeding with bioactive forages (Nansen et al., 1987, Peña-Espinoza et al., 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In all the genotypes, crude protein content was the highest in first cutting while it was lowest in the third cutting. Espinoza et al (2016) reported that after first cutting, the chicory exhibited the very limited regrowth and, therefore the lower protein content. Previously, it was reported that crude protein content of chicory ranged between 16.20 and 20.07% (Piluzza et al, 2014;Espinoza et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…For goats on farms in other countries, FEC were lower for ensiled cassava (which contains tannins) compared to sun dried [13], lower for silage, hay and fresh cassava compared to control diets [14] and lower for cassava silage compared to grass and grass/soybean meal supplemented goats [15]. More recently, in cattle, chicory silage reduced worm burdens and/or FEC in two studies [16]. These studies, combined with results of the present study, indicates that ensiling does not significantly alter the ability of tannin-containing plants to negatively influence FEC.…”
Section: Discussionmentioning
confidence: 99%